Pembebanan Hypotek Atas Kapal Laut dalam Perjanjian Kredit Bank - Dimas Hadi Prastya; I Nyoman Putu Budiartha; Desak Gd.Dwi Arini (Fakultas Hukum Universitas Warmadewa, 2020)
The Bank temporarily gives or disburses credit to usually preceded by an agreement that is usually called a draft loan agreement. In the loan agreement, there is a statement, as collateral when paying the credit, the agreement of the debtor is in default. In the banking practice specifically credit problems are known to have various institutions. While seen from the object there is a collateral institution of the owner of movable and inanimate objects. The formulation of the problem in this paper is 1) What are the conditions that must be met by the imposition of a mortgage on a ship in a bank credit agreement? and 2) What is the procedure for loading a mortgage on a ship in a bank credit agreement? This type of research used in this research is Empirical Legal Research that is taking facts that occur in the field, obtained through explanations from informants and can be understood by understanding the real law or in accordance with community life in society. The results of this study are, 1) Requirements that must be approved for the imposition of mortgages on marine vessels in a bank credit agreement, namely ships that have entered and are listed in the Indonesian ship list, the owner of the ship that receives a mortgage and who wants to accept individuals for ship assistance (made in in the presence of a Notary) 2) procedures for loading a mortgage on a ship in an approved bank credit agreement and the counter registrants of the ship list are approved for completeness of administration in less than 5 (five) days agreed upon when the documents are received as summarized. Ships that have entered the shipping list and other vessels in the process and parts of the ship that can be given mortgage rights. Like a ship that is burdened with a mortgage, the mortgage recipient is given a ship mortgage deed that has the same executorial power as the result of a trial that has permanent and easy legal power. Sanctions due to mortgage regulations for marine vessels are emphasized in order to prevent arbitrariness from the Office of the Harvesting Office and Port Authority in managing mortgage loading for ships.